2016
DOI: 10.5603/cj.a2015.0070
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of admission red cell distribution width-platelet ratio for no-reflow phenomenon in acute ST segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Background: The red cell distribution width-platelet ratio (RPR), a novel inflammatory marker is currently used to predict inflammation in chronic diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 24 publications
3
44
1
Order By: Relevance
“…Hematological parameters including hemoglobin level, leukocyte, neutrophil and lymphocyte counts, Mean Platelet Volume (MPV) and ratios including Neutrophil/Lymphocyte Ratio, Red Cell Distribution Width (RDW), Platelet Distribution Width (PDW) are demonstrating measure of the general inflammatory activity which provides prognostic information related to some ischemic disorders (4)(5)(6). It gives also economic and fast information about inflammation that is responsible for the pathogenesis of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological parameters including hemoglobin level, leukocyte, neutrophil and lymphocyte counts, Mean Platelet Volume (MPV) and ratios including Neutrophil/Lymphocyte Ratio, Red Cell Distribution Width (RDW), Platelet Distribution Width (PDW) are demonstrating measure of the general inflammatory activity which provides prognostic information related to some ischemic disorders (4)(5)(6). It gives also economic and fast information about inflammation that is responsible for the pathogenesis of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cardiovascular diseases are characterized by subclinical inflammation. A novel, inexpensive, and easily calculated index, red cell distribution width-platelet ratio (RPR) is used in clinical practice for predicting mortality in patients with chronic diseases [10]. RPR is currently studied as an inflammatory marker and predictor of several cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We have read the article "Predictive value of admission red cell distribution width-platelet ratio for no-reflow phenomenon in acute ST segment elevation myocardial infarction undergoing primary percutaneous coronary intervention" by Celik et al [1]. The authors have concluded that admission neutrophil-lymphocyte ratio, platecrit, and red cell distribution width-platelet ratio are independent correlates of no-reflow and in-hospital major adverse cardiac events (MACEs) among patients with ST segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI).…”
Section: Myocardial Blush Grade and Thrombolysis In Myocardial Infarcmentioning
confidence: 99%